Hemorheological Alterations in Patients with Heart Failure with Reduced Ejection Fraction Treated by Resveratrol - Roland Gal; Dora Praksch; Peter Kenyeres; Miklos Rabai; Kalman Toth; Robert Halmosi; Tamas Habon (Cardiovascular Therapeutics)
Objectives. Several beneficial effects of resveratrol have already been published. This study evaluated the effect of resveratrol on the hemorheological parameters in patients with heart failure with reduced ejection fraction. Methods. In our double-blind, placebo-controlled human clinical trial, we enrolled 60 outpatients with heart failure. Patients were randomized into two groups: receiving either 100 mg resveratrol capsule daily or placebo for 3 months. Hematocrit was determined by microhematocrit centrifuge. Plasma and whole blood viscosity was evaluated by capillary viscometer. Erythrocyte aggregation was measured by both LORCA and Myrenne aggregometers. LORCA ektacytometer was used for measuring erythrocyte deformability. Exercise capacity was assessed by a 6-minute walk test. Results. Resveratrol treatment did not have any significant effect on hematocrit and viscosity. The erythrocyte deformability also remained unchanged. However, significant improvement of red blood cell aggregation was observed in the resveratrol group compared to baseline after 3 months. Furthermore, positive correlation was found between the exercise capacity and the hemorheological properties (Hct, WBV, and RBC aggregation and deformability) as well. Conclusion. These findings indicate that resveratrol can significantly reduce red blood cell aggregation, which may positively influence microcirculation, which may contribute to the improvement of tissue perfusion and oxygen supply in heart failure.